Mental Health in the progress of the COVID-19 Pandemic: Conceptions of Primary Health Care workers (Research, Society and Development, 2020)
Objective: to understand the perceptions of the workers of the Family Health team about the outcome of the COVID-19 pandemic in the demands of mental health in the context of Primary Care, with a view to contributing to studies that are still scarce on the subject. Methodology: this is a qualitative research of an exploratory-descriptive character, carried out in a municipality in the metropolitan region of Recife. Professionals from the Family Health team participated in the research, with data collected through research using semi-structured questionnaires from August to September 2020 and displacement by way of Discourse Analysis. Results and discussion: they present categories of the speeches of nine workers, two from higher education and seven from secondary education. It emerged from the speeches, a set of promotion of the pandemic of the new coronavirus in the demands of mental health in the territory where Primary Care operates, resulting from the strategies of distancing and social isolation, as which reached users and professionals, increase the increase in cases of psychological distress and compromised the quality of care actions in this space. Conclusion: this study values the visualization of the pandemic as a social phenomenon and its repercussions on the population's mental health, placing the need to think and plan that go beyond the biological effects caused by the virus and extend the integrality of the subjects and the care in the territory.